(18)F-FDG PET/CT for Monitoring of Ipilimumab Therapy in Patients with Metastatic Melanoma - Ito, Kimiteru (J Nucl Med, 2019)
Immune checkpoint inhibitors (ICIs) are now commonly used to treat patients with metastatic malignant melanoma. Although concerns have been raised that the inflammatory response induced by ICIs may limit the ability of (18)F-FDG PET/CT to assess tumor response, systematic analyses on the use of (18)F-FDG PET/CT in this setting are mostly lacking. Thus, we set out to evaluate the association between tumor response on (18)F-FDG PET/CT and prognosis in patients with metastatic malignant melanoma treated with ipilimumab. Methods: We analyzed 60 consecutive patients with metastatic melanoma who underwent (18)F-FDG PET/CT scans both before and after treatment to evaluate treatment response after completion of ipilimumab therapy. Tumor response was assessed by the change in the sum of SULpeak (voxels with the highest average SUL [SUV normalized to lean body mass]) of up to 5 lesions according to PERCIST5. New lesions on PET that appeared suggestive of metastases were considered progressive metabolic disease (PMD). Because immunotherapy may cause new inflammatory lesions that are detectable on (18)F-FDG PET/CT, we also evaluated an immunotherapy-modified response classification (imPERCIST5). In this classification, new lesions do not define PMD per se; rather, PMD requires an increase in the sum of SULpeak by 30%. The correlation between tumor response according to these 3 definitions and overall survival (OS) was evaluated and compared with known prognostic factors. Results: In responders and nonresponders, the 2-y OS was 66% versus 29% for imPERCIST5 (P = 0.003). After multivariate analysis, imPERCIST5 remained prognostic (hazard ratio, 3.853; 95% confidence interval, 1.498–9.911; P = 0.005). New sites of focal (18)F-FDG uptake occurred more often in patients with PMD (n = 24) by imPERCIST5 than in those with stable metabolic disease (n = 7) or partial metabolic response (n = 4). In patients with partial metabolic response, 2 of 4 isolated new lesions regressed spontaneously during follow-up. Conclusion: In patients with metastatic melanoma treated with ipilimumab, tumor response according to PERCIST was associated with OS. Our data suggest that PMD should not be defined by the appearance of new lesions, but rather by an increase in the sum of SULpeak.